SIMPLE ADDITIVE WEIGHTING METHOD AS A DECISION- MAKING MODEL FOR DETERMINING FRUIT QUALITY BANANA SEEDS IN TANGGAMUS LAMPUNG - Meyla Nurvita; Siti Mukodimah (International Journal of Artificial Intelligence and Robotic Technology, 2021)
Banana is a fruit that is very easy to find anywhere and anytime, because of its nature that can bear fruit at any time without waiting for the season to come like other fruits , especially in tropical regions such as the country of Indonesia and because of the many types and kinds of this fruit, ranging from those the size of a little finger to those that are the size of an avocado, all taste very sweet. Bananas are also associated with the local culture, examples of certain types of bananas are usually used as ubo rampes from a certain traditional ceremony. The study was conducted to determine the quality of banana fruit seeds in Tanggamus Lampung which was carried out using the Simple Additive Weighting method is one of the weighted summation methods. The basic concept of the Simple Additive Weighting method is to look for weighted summations with performance ratings on each alternative on all attributes. This aims to facilitate the research process of the results of this study. The results of the study conducted were based on calculations above V1 (weight of banana mas) = 0.875%, V2 (weight of banana pupae) = 0.725%, and V3 (weight of banana horn) = 0.6%.